2021
DOI: 10.3390/ijms22020907
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Traumatic Brain Injury Causes Neuroinflammation before Tau Pathology in Adolescent P301S Mice

Abstract: Repetitive closed head injury (rCHI) is commonly encountered in young athletes engaged in contact and collision sports. Traumatic brain injury (TBI) including rCHI has been reported to be an important risk factor for several tauopathies in studies of adult humans and animals. However, the link between rCHI and the progression of tau pathology in adolescents remains to be elucidated. We evaluated whether rCHI can trigger the initial acceleration of pathological tau in adolescent mice and impact the long-term ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…11 ). However, in agreement with our post-injury results, repetitive closed head injury increased the microglial response in PS19 mice [ 42 ]. The PS19 prion promoter may be advantageous in the context of tau spreading, which was accelerated after a moderate-severe penetrating TBI, and resulted in learning and memory impairment [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…11 ). However, in agreement with our post-injury results, repetitive closed head injury increased the microglial response in PS19 mice [ 42 ]. The PS19 prion promoter may be advantageous in the context of tau spreading, which was accelerated after a moderate-severe penetrating TBI, and resulted in learning and memory impairment [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Existing research have primarily demonstrated a statistical link rather than a definitive causal relationship between specific mechanisms and the disease. Studies discovered that the accumulation of amyloid β might trigger an inflammatory reaction, and subsequent processes resulting from these inflammatory changes may be the underlying cause of the disease in PSCI ( Lalancette-Hébert et al, 2012 ; Ott et al, 2018 ; Izzy et al, 2021 ). Likewise, oxidative stress can impact the integrity of neurons and the expression of genes, which in turn affects cognitive performance by causing changes in the structure of hippocampal dendrites ( Chi et al, 2023 ).…”
Section: The Clinical Application Prospect Of Multi-omics In Pscimentioning
confidence: 99%
“…Microglia are essential to the healthy brain, as they contribute to many brain functions and help sustain the physiological brain structure [ 83 , 214 , 215 ]. Belonging to the innate immune system of the brain, microglia contribute to an immune response against any brain-invading agent [ 35 , 216 , 217 ], as well as following traumatic and neurovascular brain damage [ 218 , 219 , 220 ]. They help with resolving tissue damage and support regeneration and restauration of structure and function [ 74 ].…”
Section: The Role Of Microglia In Viral Brain Infections Accelerating Brain Agingmentioning
confidence: 99%